Kajian Pencahayaan Alami dan Buatan Terhadap Kenyamanan Visual Pengunjung di Kame Bakehouse Bandung - Jecinta Abigail; Carina Tjandradipura; Yunita Setyoningrum (Serat Rupa: Journal of Design, 2026)
The development of flexible working patterns has encouraged bakehouses to function as multi-activity spaces for dining, working, and social interaction, thereby requiring visual comfort through lighting that can support activities without causing glare or eye fatigue. This study aims to analyze the implementation of natural and artificial lighting in the interior of Kame Bakehouse Bandung and its relationship to visitors’ visual comfort. This research employed a descriptive approach supported by quantitative data through lighting intensity measurements using a lux meter at eight spatial zones. Data were collected through field observations, visitor questionnaires, and visual documentation. The measurement results were compared with the lighting standards of SNI 6197:2020 and correlated with visitors’ perceptions of visual comfort. The findings indicate a significant discrepancy in several areas where lighting intensity has not fully met the standards and where glare potential occurs due to the dominance of natural lighting. Nevertheless, questionnaire results revealed that visitors still reported a high level of visual comfort. The study demonstrates that visual comfort in commercial spaces is not solely determined by technical standards, but also influenced by ambience and user activities. This research concludes that a more flexible lighting integration strategy is necessary to improve the interior design quality of bakehouses without neglecting the psychological aspects of spatial users.